Zgodovina raziskovanja luminiscentnih snovi - Južnič, Stanislav (Vakuumist, 1996)
The development of the research of the luminiscent materials is described frominventions to their use in Braun's cathode ray tube. Attention is put on the researches and writing about luminiscence in Austria, specially in its Slovene part. First part of the article ends with Stokes' law in the middle of last century.
Keywords: fizika; physics; luminiscenca; zgodovinski prikazi